THE EFFECT OF SUPERVISION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH COMPENSATION AS AN INTERVENING VARIABLE IN PUBLIC WORKS DEPARTMENT AND SPATIAL MANAGEMENT OF THE CITY OF BINJAI - Ridho Indah Purnama; Isa Indrawan (Lafadz Jaya Publisher, 2023)
This research uses associative quantitative research. The data source used is primary data. This research was conducted at the Office of Public Works and Spatial Planning in Binjai City. The population of this study was 79 employees. and the measuring tool is samrt pls version 3.3.3. This research was conducted to see the effect of supervision and work discipline on employee performance with compensation as an intervening variable. The results of this study are that Work Discipline has no significant positive effect on Employee Performance. Work Discipline has no significant positive effect on Compensation. Compensation has a positive and significant effect on employee performance. Supervision has no significant positive effect on employee performance. Supervision has a positive and significant effect on Compensation. Work Discipline has no significant positive effect on Employee Performance through Compensation. Supervision has a positive and significant effect on Employee Performance through Compensation.